1998
DOI: 10.1002/mds.870130108
|View full text |Cite
|
Sign up to set email alerts
|

Living with a person who has parkinson's disease: The Spouse's perspective by stage of disease

Abstract: The objective of this study was to examine the experience of spouses caregiving for their spouse with Parkinson's disease (PD) and to determine whether their experiences differed by stage of disease. By using a cross-sectional design and mail questionnaire data from 380 spouse caregivers across 23 sites of the Parkinson Study Group, key caregiver variables were examined by stage of PD. Three categories of variables--caregiver role strain (10 measures), caregiver situation (four measures), and caregiver charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
201
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(219 citation statements)
references
References 18 publications
12
201
4
2
Order By: Relevance
“…It is also important to consider the needs of the caregiver. Caregivers perform an average of 23 tasks per day on behalf of patients with stage III PD, and 30 for patients in stage IV/V of the disease, 962 underscoring the physical burden they bear. In the early stages, it may only be necessary to provide educational and support ser- vices.…”
Section: Nonpharmacologic Treatments For Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to consider the needs of the caregiver. Caregivers perform an average of 23 tasks per day on behalf of patients with stage III PD, and 30 for patients in stage IV/V of the disease, 962 underscoring the physical burden they bear. In the early stages, it may only be necessary to provide educational and support ser- vices.…”
Section: Nonpharmacologic Treatments For Pdmentioning
confidence: 99%
“…Education provides the patient with PD and their caregiver with an understanding of their disease and a sense of control even as the disease continues to progress. 962 Conversely, patients and caregivers should be aware that in the early stages of PD, knowledge of the potential consequences of the disease can be alarming and anxiety provoking. At this stage, selective or at least filtered information is generally more helpful.…”
Section: Nonpharmacologic Treatments For Pdmentioning
confidence: 99%
“…In the study, questionnaires were mailed to caregivers and found that they had to perform significantly greater numbers of tasks for the patient, their burden increased and their own health became significantly poorer as their charge's disease progressed. 70 In PD management therefore, the patient's perspective is important and should be recognised. Several of the measures for assessing HRQoL in PD are designed to capture this perspective and their regular use enables better global assessment of all the symptoms that are causing difficulties and distress and informs better treatment choices.…”
Section: The Patient's Perspectivementioning
confidence: 99%
“…Strain increases with disease severity and can lead to a decline in the physical and emotional health of the caregiver. 3 The first step for managing caregiver strain is to measure the strain severity. This can be done through standardized caregiver strain scales.…”
Section: Caregiver Strainmentioning
confidence: 99%